Improving the Skills to Explore the Environment through the Drill Method in Class VIII Blind Student: (Classroom Action Research in SLBN Prof. Dr. Sri Soedewi MS, SH City Jambi) - Jaya Saputra; Asep Ahmad Sopandi (Edumaspul: Jurnal Pendidikan, 2022)
The research discusses the improvement of environmental exploration skills through the drill method in class VIII blind students at SLB Negeri Prof. Dr. Sri Soedewi Masjchun Sofwan, SH Jambi City. This research is based on the problem of blind students who are not yet skilled in exploring the environment. This class has 2 blind students with the initials E and H with different characteristics. The research aims to see whether the drill method is effectively used to improve the skills of blind students in exploring the environment. The research was conducted using classroom action research methods. This research was conducted by collaborating with teachers. This research was conducted in two cycles. Each cycle starts from the stages of planning, execution of actions, observation and reflection. The results of the study are described in the form of narratives and graphs from the process to the results of the increase in cycle II. In the first cycle, students get the results E 65% dan H 65% and the results in the second cycle E 95% and H 90%. This shows that the drill method is effectively used to improve environmental exploration skills.